Collaborative Governance dalam Pelestarian Seni Tradisional: Studi Pada Wayang Orang Ngesti Pandawa Kota Semarang - Aji, Nawangsasi Wincahyo Artiko; Asih Widi Lestari; Renata Jati Nirmala (Public Administration Dept, Faculty of Social and Political Science, 2025)
This study examines the dynamics of collaborative governance in traditional art preservation efforts, highlighting the case of Wayang Orang Ngesti Pandawa (WONP) in Semarang City. The approach used is descriptive qualitative with guidance from Emerson et al.'s (2012) Collaborative Action Framework. Data were collected through in-depth interviews, field observations, document analysis, and literature review. Data validity was ensured through triangulation and member checking techniques. The results showed the involvement of various stakeholders, such as local government, art communities, universities, and civil society. They collaborated in various activities, such as organizing cultural festivals, joint performances, and training programs. This collaboration increases public participation, supports the regeneration of artists, and strengthens cultural sustainability. However, there are still obstacles in the form of limited institutional capacity, unstructured funding mechanisms, and power imbalances between parties. Although this study focuses on the context of Semarang, the results have comparative relevance for other regions that wish to apply a collaborative approach to cultural heritage management. Practically, this study provides recommendations for strengthening multi-stakeholder coordination in preserving intangible cultural heritage. Socially, this study emphasizes the importance of inclusive strategies in strengthening local cultural identity. The originality of this study lies in its empirical contribution to understanding how a collaborative framework can be effectively applied to preserve traditional arts amid modern challenges.